Non-Equilibrium Thermodynamics with Linear Modes in Tribo-couplings (Part I) - Janahmadov, A.Kh.; Volchenko, D.A.; Volchenko, N.A.; Skrypnyk, V.S.; Zhuravlev, D.Yu.; Маlyk L.B. (Herald of Azerbaijan Engineering Academy, 2022)
The article examines the following questions: thermal conductivity and thermoelectric phenomena in tribo-couplings; electro-kinetic phenomena and chemical reactions in tribo-couplings; the discussion of the results. An algorithm of non-equilibrium thermodynamics is proposed, which contains thermal conductivity and thermoelectric phenomena in a non-massive metal friction element and electrokinetic phenomena in the near-surface layers of a polymer lining. In linear modes of operation of friction pairs of brakes, it is shown that due to the cross effect with temperature gradients for metal elements, two equilibrium states are revealed - a steady surface temperature and a thermal stabilization state; for a polymer lining, the equilibrium state is considered to be the burnout of the binder components from its near-surface layer with the formation of liquid islands. The flow of electrokinetic phenomena in the nearsurface layer of the polymer lining and the determination of: the potential of the fluid flow and the resulting electric current; effect of electro-osmosis and liquid pressure. From the above parameters, ratios are formed that are equal to the Onsager and Saxen ratios, which makes it possible to determine the parameters by calculation.